Neonatal unit (NU) Infant Medical Trauma and the lifelong implications for children and their families - Rupa Rubinstein; Narendra Aladangady (Frontiers in Psychology, 2026)
Introduction Infant Medical Trauma (IMT) is a result of prolonged toxic experiences usually experienced by patients in the neonatal unit (NU), and is associated with significant sequalae. Method This article describes the pathophysiology of IMT and the short- and long-term impacts. The possible methods of minimising this is discussed. Results Increased neonatal staff and parent awareness of IMT could encourage clustering of care, improved use of tools for recognition of pain and further highlight the benefits of family-integrated care and skin-to-skin care. Conclusion While IMT may be considered a consequence of survival from the NU, it’s effects can be minimised with a range of techniques to protect the patients (and parents) from psychological harm.